If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 6 = -3x Reorder the terms: 6 + 5y = -3x Solving 6 + 5y = -3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5y = -6 + -3x Combine like terms: 6 + -6 = 0 0 + 5y = -6 + -3x 5y = -6 + -3x Divide each side by '5'. y = -1.2 + -0.6x Simplifying y = -1.2 + -0.6x
| 3x-5(x-3)=2(10-x) | | h(2h-4)+(h+5h-9)-(3h+7h-6)= | | 4(h-1)=6h+4+2h | | -2/5(10x-25)=8x+4 | | 1/3(2b+9)=2/3(1b+9/2) | | 2(4x5)/2(4-2) | | 3/x/3/x | | 9/60 | | 21/11=n/44 | | x+3/10=73 | | 250/2 | | -0.10(106)+0.90x=0.05(x-8) | | -4(3-6d)=2d-2 | | 2x+80=5x+44 | | y-17/19=-13/19 | | 30=0.3x | | 6+2x=102 | | (N+0)+(n+1)=-389 | | w^2=77 | | 8.5+j=17.6 | | 7x=6x+72 | | 5/3x+1/3x=211/3+7/3x | | 392/2 | | 1/12+3/8y=5/12 | | 5x+26(x-2)=103 | | 5(5x+22)=5 | | 4x-45=x^2 | | derp= | | KLN=9x-7 | | -(3a+4a-6)+2(9a+3)+3(-8a)= | | 2(11m-10)+6m=-6(-6m+2)-8 | | 13m-5=4m |